The "Hand-in" Project: Jump-starting Communication Between Inpatient and Outpatient Providers. Issue 11 (November 2017) - Holleck, Jürgen L.; Gunderson, Craig G.; Antony, Sheila M.; Gupta, Shaili; Chang, John J.; Merchant, Naseema; Lin, Shin; Federman, Daniel G.
Abstract : Objectives: Communication between hospitalists and primary care providers (PCPs) upon discharge has been much discussed, but the transition from outpatient to inpatient has received less attention. We questioned whether a brief, standardized e-mail from the hospitalist to the PCP upon admission could facilitate information exchange, increase communication, elucidate PCP preferences, and improve outcomes. Methods: This prospective single-center study with a preintervention-to-postintervention design involved 300 inpatient admissions from June 2015 through October 2015 in the Veterans Affairs Connecticut Healthcare System. Hospitalists e-mailed an encrypted notification of admission along with standardized questions to PCPs within 1 day of admission. Measurements included the number of communications between PCPs and hospitalists, length of stay (LOS), 30-day readmissions, 30-day emergency department (ED) utilization rates, PCP preferences with regard to communication, and follow-up. Results: Preintervention data for 94 patients during a 6-week period revealed 0.11 communications per patient, an LOS of 4.18 days, 30-day readmissions of 28.7%, and 30-day ED visits of 32%. Postintervention data on 206 patients during the next 12 weeks showed statistically significant increased communications per patient (0.5), and a nonsignificant decrease in LOS (3.96 days), 30-day readmissions (22.3%), and 30-day ED visits (31%). P values were <0.001, 0.67, 0.4, and 0.79, respectively. PCPs preferred e-mail communication upon discharge (40%) to telephone (25%) or instant messaging (13%), and 39% wanted a follow-up appointment within 2 weeks, regardless of what transpired. Conclusions: A hospitalist-led transition-of-care intervention designed to improve communication and information exchange between PCPs and hospitalists at the time of admission demonstrated that encrypted e-mail could be used as a tool to obtain useful additional medical and psychosocial information and to better understand PCP attitudes and preferences. The increased level of communication did not yield statistically significant decreases in LOS, 30-day readmission rates, or 30-day post-discharge ED visits, however. Abstract : Communication during the "handoff" that occurs upon hospital discharge has been emphasized, whereas the "hand-in" transition of care upon admission has received much less attention. The authors' hospitalist-led transition-of-care intervention demonstrated that encrypted e-mail to primary care physicians upon patient admission can increase communication, facilitate information exchange, and elucidate physician preferences, although outcomes were unaffected.